President's Annual Report, 1992-1993 - Bailey, Hugh C. (Valdosta State University Archives and Special Collections, 2013)
The Valdosta State College Annual Report of the President for fiscal year 1992-1993 by Hugh C. Bailey
Keywords: Valdosta State University; College publications; Corporate reports; College presidents